Research handbook on UN sanctions and international law - Herik, Larissa van den, 1975- (Research handbooks in international law, 2017)
The twenty-five years following the conclusion of the Cold War witnessed an unprecedented intensification of the usage of UN sanctions. This Research Handbook maps how UN sanctions multiplied and diversified during this period and analyses the substantive and procedural transformations to UN sanctions regimes, through the lens of international law. Expert contributors explore different types of UN sanctions regimes, most notably counter-terrorism regimes, counter-proliferation regimes and conflict-resolution regimes. They trace developments across these regimes, such as increased references to international legal standards in sanctions design and procedure as well as interplays with other processes and informal arrangements. Key chapters also specifically examine synergies between UN sanctions and unilateral measures and explore the different legal frameworks that shape and govern these respective regimes. Offering a holistic study of UN sanctions, this Research Handbook identifies cross-cutting issues and common challenges in order to provide an outlook on the future of UN sanctions in a 21st century setting. Comprehensive and engaging, students and scholars of international law and human rights law, as well as international relations more widely, will find this book an essential companion. Its forward-thinking approach will also benefit legal practitioners at the UN, other international organisations and law firms.